Photoluminescence in quantum-confined SnO2 nanocrystals: Evidence of free exciton decay - Lee, EJH; Ribeiro, C.; Giraldi, T. R.; Longo, Elson [UNESP]; Leite, E. R.; Varela, José Arana [UNESP] (American Institute of Physics (AIP), 2004)
Nanocrystalline SnO2 quantum dots were synthesized at room temperature by hydrolysis reaction of SnCl2. The addition of tetrabutyl ammonium hydroxide and the use of hydrothermal treatment enabled one to obtain tin dioxide colloidal suspensions with mean particle radii ranging from 1.5 to 4.3 nm. The photoluminescent properties of the suspensions were studied. The particle size distribution was estimated by transmission electron microscopy. Assuming that the maximum intensity photon energy of the photoluminescence spectra is related to the band gap energy of the system, the size dependence of the band gap energies of the quantum-confined SnO2 particles was studied. This dependence was observed to agree very well with the weak confinement regime predicted by the effective mass model. This might be an indication that photoluminescence occurs as a result of a free exciton decay process. (C) 2004 American Institute of Physics.